High Efficiency Gaseous Tracking Detector for Cosmic Muon Radiography. (5th December 2016) - Varga, Dezső; Nyitrai, Gábor; Hamar, Gergő; Oláh, László
Abstract : A tracking detector system has been constructed with an innovative approach to the classical multiwire proportional chamber concept, using contemporary technologies. The detectors, covering an area of 0.58 square meters each, are optimized for the application of muon radiography. The main features are high (>99.5%) and uniform detection efficiency, 9 mm FWHM position resolution, and filling gas consumption below 2 liters per hour for the nontoxic, nonflammable argon and carbon dioxide mixture. These parameters, along with the simplicity of the construction and the tolerance for mechanical effects, make the detectors a viable option for a large area muography observation system.